Influence of enteral feeding and anemia on tissue oxygen extraction after red blood cell transfusion in preterm infants. Issue 3 (26th January 2020) - Goldstein, Gregory P.; Rao, Anoop; Ling, Albee Y.; Ding, Victoria Y.; Chang, Irene J.; Chock, Valerie Y.
Abstract : BACKGROUND: Understanding factors that impact tissue oxygen extraction may guide red blood cell (RBC) transfusion decision making in preterm infants. Our objective was to assess the influence of enteral feeding and anemia on cerebral and mesenteric oxygen saturation (Csat and Msat) and fractional tissue oxygen extraction (cFTOE and mFTOE) over the entire time course of RBC transfusion. STUDY DESIGN AND METHODS: Preterm, very low‐birth‐weight infants receiving RBC transfusions at a single center were enrolled. Near‐infrared spectroscopy sensors measured Csat and Msat levels from an hour before transfusion to 24 hours after. During this period, changes in Csat, Msat, cFTOE, and mFTOE were described, and their association with enteral feeding status and pretransfusion degree of anemia were assessed using generalized estimating equations. RESULTS: RBC transfusion data from 31 preterm infants were included. Infants receiving enteral feeds exhibited lower pretransfusion Msat. Infants with pretransfusion hematocrit greater than 30% exhibited higher pretransfusion Csat and lower pretransfusion cFTOE. Such differences in baseline measurements persisted through 24 hours after transfusion. However, no statistically significant differences in oxygenation measures over time by enteral feeding or anemia status were identified. CONCLUSION: Compared to NPO, enteral feeding was associated with lower Msat; anemia (hematocrit ≤30%) was associated with lower Csat and higher cFTOE. Over the time course of RBC transfusion, trajectories of Csat, Msat, cFTOE and mFTOE did not differ by enteral feeding or anemia status.